Neglected complete bilateral achilles tendon rupture. clinical case presentation, treatment and follow-up - Polidoro, Federico; Rea, Roberto; Fascione, Fabrizio; Salini, Vincenzo; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: subcutaneous Achilles tendon lesions are common degenerative tendon tears, often related to sport activities, multiple pharmacotherapies and internal medical comorbidities. Neglect an Achilles tendon lesion can affect walk ability, while neglect a bilateral lesion could really lead to a serious limitation of self-sufficiency in daily living. We report a case of chronic bilateral Achilles tendon lesion successful treated with LARS augmentation, along with some clinical considerations concerning the clinical outcome. Methods: we report a case of a chronic bilateral Achilles tendon lesion in an elderly man with multiple comorbidities, successful treated with LARS reconstruction, along with some considerations concerning possible intraoperative issues and the clinical outcome. Results: good functional result was obtained as documented with pre and postoperative American Orthopedic Foot And Ankle Society Scale and the “Foot And Ankle Disability Index”, without complications. Conclusions: a bilateral Achilles tendon rupture is a very disabling pathology, that needs prompt diagnosis and treatment to prevent further complications. LARS reconstruction could be an effective method in selected patients to avoid some intraoperative issues related to patient comorbidities and ability to follow complex postoperative rehabilitation protocols. (www.actabiomedica.it)